2006
DOI: 10.1175/jam2407.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of Tropical Cyclone Parametric Wind Models Tailored for Midlatitude Application—Preliminary Results

Abstract: Over the years, researchers have developed parametric wind models to depict the surface winds within a tropical cyclone (TC). Most models were developed using data from aircraft flights into low-latitude (south of 30°N) TCs in the Atlantic Ocean, Gulf of Mexico, and Caribbean Sea. Such models may not adequately reproduce the midlatitude TC wind field where synoptic interaction and acceleration are more pronounced. To tailor these models for midlatitude application, latitude-dependent angular size and shape det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Various improvements have been made in recent years, including the addition of stepped-frequency microwave radiometer data in the analysis (Mark Powell 2007, personal communication). The H*Wind dataset is considered by hurricane experts to be the best available source of over-ocean wind field information (David Nolan and Jeff Kepert, 2008, personal communication) and has been used in previous modelling work on hurricane windfields (Macafee and Pearson, 2006). For the above reasons, we use the H*Wind data as the validation dataset in this work.…”
Section: Data and Comparison Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various improvements have been made in recent years, including the addition of stepped-frequency microwave radiometer data in the analysis (Mark Powell 2007, personal communication). The H*Wind dataset is considered by hurricane experts to be the best available source of over-ocean wind field information (David Nolan and Jeff Kepert, 2008, personal communication) and has been used in previous modelling work on hurricane windfields (Macafee and Pearson, 2006). For the above reasons, we use the H*Wind data as the validation dataset in this work.…”
Section: Data and Comparison Methodsmentioning
confidence: 99%
“…The steady pressure gradient is used to drive momentum equations, which can be used to obtain a model for the wind. Following previous work (Kepert, 2001;Macafee and Pearson, 2006), we prescribe a radially symmetric pressure gradient using partial derivatives of a Holland profile (Holland, 1980), given by p(r) = p c + (p n − p c )e…”
Section: Models Testedmentioning
confidence: 99%
See 1 more Smart Citation
“…Many parametric typhoon models have been developed to provide meteorological information for storm surge or storm wave modeling [41][42][43][44][45][46]. Since the authors of [47] found that the analytical models provided very similar results, the parametric typhoon model proposed in [43] was employed:…”
Section: Model Forcingmentioning
confidence: 99%
“…A common way to generate wind and air pressure fields for typhoons is to reconstruct them using the analytical parametric cyclone model. Over the years, many parametric cyclone models have been developed to provide meteorological information for storm surge modeling [43][44][45][46][47][48]. Jakobsen and Madsen [49] investigated and compared parametric cyclone models based on cyclone position, central pressure, maximum wind speed and radius to maximum wind speed.…”
Section: Parametric Cyclone Modelmentioning
confidence: 99%